PENGUATAN LITERASI HAK KONSUMEN DAN PEMBENTUKAN KOMUNITAS KONSUMEN KRITIS MELALUI KOLABORASI PENTAHELIX DI UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Muthia Sakti; Suherman; Rianda Dirkareshza; Abdu El-Aziz Attamimi; Niti Emiliana; Rio Priambodo; Dwi Rahayu Ningrum (Zhata Institut, 2026)
Low financial literacy amidst high digital service access leaves society, particularly university students, vulnerable to detrimental financial practices such as online loan traps and hidden costs. Universitas Pembangunan Nasional Veteran Jakarta was selected as the partner location based on the strategic demographic of students as the younger generation and the institution's commitment to national defense and sustainability values. This activity was implemented using the Plan-Do-Check-Action (PDCA) framework, which integrates a pentahelix collaborative approach to ensure systematic program execution and measurable impacts. The community service results demonstrated a significant 25.7% increase in participants' financial literacy and consumer rights awareness, with the average score rising from 3.35 to 4.14. Furthermore, the program successfully fostered critical awareness among students regarding the connection between financial systems and the climate crisis while initiating the formation of the Consumer Sustainability Community as an advocacy platform. This cross-sector synergy proved effective in establishing an educational ecosystem that empowers students to become responsible and legally literate consumers in the digital financial era.